Исследование колебаний с учетом рассеяния энергии в материале в трудах украинских ученых. Основание школы Г. С. Писаренко - Ларин, Андрей Алексеевич (Днепропетровский национальный университет им. О. Гончара, 2010)
Представлена история развития расчетов колебаний механических систем с учетом рассеяния энергии в материале. Рассматривается вклад в решение этой проблемы украинских ученых, в первую очередь Г. С. Писаренко и А. Д. Коваленко.

In article the history of development of the accounts of vibrations of mechanical systems subject to the energy dissipation in material is submitted. Its application for the decision of problems of Ukrainian scientists, first of all G. S. Pisarenko and A. D. Kovalenko is covered.
Keywords: теория механических колебаний; рассеяние энергии; логарифмический декремент колебаний; петля гистерезиса; турбинные лопатки; theory of mechanical vibrations; dissipation of energy; logarithmic decrement of vibrations; hysteresis loop; turbine buckets